Drug suicide - Värnik, Airi (2017)
Background: There is a lack of international research on suicide by drug overdose as a preventable suicide method. Sex- and age-specific rates of suicide by drug self-poisoning (ICD-10, X60-64) and the distribution of drug types used in 16 European countries were studied, and compared with other self-poisoning methods (X65-69) and intentional self-injury (X70-84). Methods. Data for 2000-04/05 were collected from national statistical offices. Age-adjusted suicide rates, and age and sex distributions, were calculated. Results: No pronounced sex differences in drug self-poisoning rates were found, either in the aggregate data (males 1.6 and females 1.5 per 100,000) or within individual countries. Among the 16 countries, the range (from some 0.3 in Portugal to 5.0 in Finland) was wide. 'Other and unspecified drugs' (X64) were recorded most frequently, with a range of 0.2-1.9, and accounted for more than 70% of deaths by drug overdose in France, Luxembourg, Portugal and Spain. Psychotropic drugs (X61) ranked second. The X63 category ('other drugs acting on the autonomic nervous system') was least frequently used. Finland showed low X64 and high X61 figures, Scotland had high levels of X62 ('narcotics and hallucinogens, not elsewhere classified') for both sexes, while England exceeded other countries in category X60. Risk was highest among the middle-aged everywhere except in Switzerland, where the elderly were most at risk. Conclusions: Suicide by drug overdose is preventable. Intentional self-poisoning with drugs kills as many males as females. The considerable differences in patterns of self-poisoning found in the various European countries are relevant to national efforts to improve diagnostics of suicide and appropriate specific prevention. The fact that vast majority of drug-overdose suicides came under the category X64 refers to the need of more detailed ICD coding system for overdose suicides is needed to permit better design of suicide-prevention strategies at national level.